Free country a tale of the Children's Crusade - Gaiman, Neil 1960-; Litt, Toby 1968-; Pollack, Rachel 1945-2023 (DC Comics, 2015)
"When several children go missing in a small English hamlet, the Dead Boy Detectives are on the case. A series of strange and unexpected twists take them to Free Country, a place that dates back a millennia, where children never grow old and are free from the abuse and tyranny of adults. But Free Country is failing and what it needs is the strength of five innately powerful children...one of whom is sorcerer Timothy Hunter...to restore their uncanny world to what it once was. This complete edition features Neil Gaiman's original THE CHILDREN'S CRUSADE #1, with artists Chris Bachalo and Mike Barreiro, along with THE CHILDREN'S CRUSADE #2 with writers Alisa Kwitney and Jamie Delano and artist Peter Snejbjerg. A brand-new middle act, written by DEAD BOY DETECTIVES writer Toby Litt, and drawn by THE BOOKS OF MAGIC artist extraodinaire Peter Gross, fully completes this compelling tale of ancient history, stolen dreams and lost children, in a way Neil Gaiman originally envisioned. Also featuring an introduction by Gaiman, and exquisite new cover art by DEAD BOY DETECTIVES artist Mark Buckingham."...Page [4] of cover
"Originally published in single magazine form as The Children's Crusade 1 & 2"...Title page verso
Keywords: Magie; Detektiv; Vermisstes Kind; Comic